Twisted-Light-Ion Interaction: The Role of Longitudinal Fields - Quinteiro, G. F.; Schmidt-Kaler, Ferdinand; Schmiegelow, Christian T. (Physical Review Letters, 2017)
The propagation of light beams is well described using the paraxial approximation, where field components along the propagation direction are usually neglected. For strongly inhomogeneous or shaped light fields, however, this approximation may fail, leading to intriguing variations of the light-matter interaction. This is the case of twisted light having opposite orbital and spin angular momenta. We compare experimental data for the excitation of a quadrupole transition in a single trapped Ca+40 ion from Schmiegelow et al. [Nat. Commun. 7, 12998 (2016)NCAOBW2041-172310.1038/ncomms12998] with a complete model where longitudinal components of the electric field are taken into account. Our model matches the experimental data and excludes by 11 standard deviations the approximation of a complete transverse field. This demonstrates the relevance of all field components for the interaction of twisted light with matter.
CRIS-Team Scopus Importer:2023-03-27